Preparation of TiC reinforced CrMo steel by 3D gel-printing. (20th October 2021) - Lin, Tao; Li, Qianghua; Song, Ke; Shao, Huiping; Yuan, Jiayun; Deng, Xin
ABSTRACT: TiC-reinforced CrMo steel was successfully fabricated by 3D gel-printing in this study. The rheological behaviour and polymerisation of slurries with different TiC content were researched. The appropriate parameters of 3D gel-printing process were found. The microstructure and phase identification of sintered samples were characterised by using scanning electron microscopy and X-ray diffraction, respectively. The relative density, bending strength and hardness of sintered bulk samples were separately measured. The results indicate that the relative density, bending strength and hardness value reach 99.8%, 2039 MPa and 51.3 HRC when TiC content is 30 wt.% in the sintered bulk samples. After oil quenching, the bending strength reaches an astonishing value 2386 MPa, and hardness is 56.1 HRC. Compared with conventional powder metallurgy methods, the mechanical properties of TiC–CrMo steel composite prepared by 3DGP are similar or even better.